Financial Inclusion and Economic Development: A Case Study of Indonesia - Muhamad Syah Isu; Bambang Bernanthos (Pelopor Publikasi Akademika, 2026)
Financial inclusion has emerged as a strategic policy priority in Indonesia, a developing country with more than 270 million people that continues to face persistent challenges of poverty and income inequality. Despite significant progress in expanding access to formal financial services, with the financial inclusion index reaching 85.1% in 2022, structural disparities across regions remain pronounced, and empirical evidence on the regional impact of financial inclusion on economic development remains limited. This research analyzes the relationship between financial inclusion and economic development in Indonesia using provincial panel data from 2016 to 2022. Financial inclusion is measured through the dimensions of access, availability, and usage of formal financial services, while economic development is represented by Gross Regional Domestic Product per capita. A fixed-effects panel data regression method is used to analyze 34 provinces with a total of 238 observations. The results show that financial inclusion has a significant positive effect on economic growth, with a coefficient of 0.425. Every 1% increase in the financial inclusion index increases GRDP per capita by 0.425%. The access dimension contributes the most compared with the availability and usage dimensions. The findings support the theory that expanding access to formal financial services drives savings mobilization, productive investment, and MSME empowerment, which ultimately accelerates inclusive economic growth in Indonesia